2018
DOI: 10.17509/ijal.v8i1.11480
|View full text |Cite
|
Sign up to set email alerts
|

Thinking critically while storytelling: Improving children’s HOTS and English oral competence

Abstract: Although studies on the development of higher order thinking skills (HOTS) as part of Bloom’s revised taxonomy have grown significantly among adult learners, little is known about its use for teaching English to young learners. In the Indonesian context, HOTS is mandated by the scientific-based 2013 national curriculum. This study investigates the development of HOTS strategies and possible challenges through storytelling among seventh grade students to improve their speaking ability. This Classroom Action Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 17 publications
0
46
0
4
Order By: Relevance
“…Related to this finding, it is crucial to understand that the knowledge of HOTS is the EFL teachers' basic weapon in order to be able to integrate HOTS in the process of teaching and learning, whether in planning stage, implementation stage, and evaluation stage. As what have stated before that teachers' knowledge of HOTS plays a crucial role in their attitude towards the implementation of HOTS itself (Setyarini et al, 2018), having the right conception of HOTS will be truly beneficial for teachers in engaging their students' HOTS in the learning process. It will be useful for students as well since teachers with good HOTS conception will direct them to the HOTS competence.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Related to this finding, it is crucial to understand that the knowledge of HOTS is the EFL teachers' basic weapon in order to be able to integrate HOTS in the process of teaching and learning, whether in planning stage, implementation stage, and evaluation stage. As what have stated before that teachers' knowledge of HOTS plays a crucial role in their attitude towards the implementation of HOTS itself (Setyarini et al, 2018), having the right conception of HOTS will be truly beneficial for teachers in engaging their students' HOTS in the learning process. It will be useful for students as well since teachers with good HOTS conception will direct them to the HOTS competence.…”
Section: Resultsmentioning
confidence: 89%
“…The study from Seman et al (2017) reveals that teacher is one of the main factors that influenced success or failure in teaching for HOTS. Moreover, Setyarini et al (2018) state that teacher's perceptions HOTS plays a crucial role in their attitude towards HOTS -based questions. Due to the importance of teachers' ability in developing HOTSbased questions, this study aimed to investigate the challenges that faced by in-service EFL teachers in developing HOTSbased questions.…”
Section: Introductionmentioning
confidence: 99%
“…These pre-service student teachers'were aware of the idea that it is the teacher's role to implement the critical thinking to their students as it is needed by the students in their future life. It is supported by [14] that critical thinking of students will appear if it was needed in a particular situation. Other responses on the statements conserning the roles of the teachers in critical thinking instructions were varying indicating the needs for more exposure on their courses which discuss and explore the teachers roles to develop their students critical thinking.…”
Section: (10%)mentioning
confidence: 99%
“…A small cohort of pre-service student teachers, who had just finished their teaching practices at schools around West Sumatra province, Indonesia, became the participants of this study. The data were collected using a "perceptions of critical thinking instruction" questionnaire that the list of its questions were proposed by [3] and then revised and added by [14]. The results showed that the pre-service student teachers, perceived CT is essential for students' development in learning.…”
mentioning
confidence: 99%
“…Still, those studies have more focus on teaching certain skills such as cognitive awareness, critical thinking, higher-order thinking skills, transfer, problem-solving skills etc. (Henderson & Wang, 2014 Apen, 2016;Li, 2016;Teng, 2016;Setyarini, Muslim, Rukmini, Yuliasri, & Mujianto, 2018).…”
Section: Introductionmentioning
confidence: 99%